PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT SINAR JERNIH SARANA (AEON DELIGHT INDONESIA) JAKARTA - Saputra, Reza; Winata, Hadi (Journal of Research and Publication Innovation, 2024)
This research aims to determine partially and simultaneously the influence of leadership and motivation on employee performance at PT Sinar Jernih Sarana (Aeon Delight Indonesia) Jakarta. This type of research is quantitative research with regression, determination and hypothesis testing. The population in this study was 80 people, the sample in this study used a saturated sample, so the research sample used was 80 respondents, the data collection technique was a questionnaire. The results of this research partially show that leadership has a significant effect on employee performance by obtaining a regression equation value of Y= 21.306+0.432 amounting to 24.2% while the remaining 75.8% was influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (4.997 > 1.991), motivation had a significant effect on employee performance by obtaining a regression equation value Y= 9.805+0.672 The determination or contribution of influence is 0.258 or 25.8% while the remaining 74.2% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (5.212 > 1.991), and simultaneously leadership and motivation had a significant effect on employee performance by obtaining a regression equation value of Y= 9.332+0.262 independent with the dependent variable obtained at 0.564, meaning that it has a moderate relationship, the value of the coefficient of determination or contribution of influence simultaneously is 31.8% while the remaining 68.2% is influenced by other factors, hypothesis testing obtained calculated F value > F table or (17.958 > 3.12),